Star Pyramids 2

Calculus Level 4

Let n n be a positive integer 5 \geq 5 .

In an n n star pyramid, find the measure of the angle between the slant height and the base that minimizes the lateral surface area when the volume is held constant.

Use two cases for n n odd and n n even.


The answer is 54.735610.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Nov 11, 2018

Case 1: n n is an odd positive integer 5 \geq 5 .

To find A s t a r : A_{star}:

m A O P = π n m\angle{AOP} = \dfrac{\pi}{n} and by Inscribed Angle Theorem m E P F = 1 2 m E O F = 1 2 2 π n = π n m A P O = π 2 n m\angle{EPF} = \dfrac{1}{2}m\angle{EOF} = \dfrac{1}{2}\dfrac{2\pi}{n} = \dfrac{\pi}{n} \implies m\angle{APO} = \dfrac{\pi}{2n}

A C O C = tan ( π n ) O C = A C tan ( π n ) \dfrac{AC}{OC} = \tan(\dfrac{\pi}{n}) \implies OC = \dfrac{AC}{\tan(\dfrac{\pi}{n})} and P C = A C tan ( π 2 n ) = r O C = r A C tan ( π n ) PC = \dfrac{AC}{\tan(\dfrac{\pi}{2n})} = r - OC = r - \dfrac{AC}{\tan(\dfrac{\pi}{n})} \implies

A C = tan ( π 2 n ) tan ( π n ) tan ( π n ) + tan ( π 2 n ) r AC = \dfrac{\tan(\dfrac{\pi}{2n})\tan(\dfrac{\pi}{n})}{\tan(\dfrac{\pi}{n}) + \tan(\dfrac{\pi}{2n})}r

A A O P = 1 2 ( tan ( π 2 n ) tan ( π n ) tan ( π n ) + tan ( π 2 n ) ) r 2 \implies A_{\triangle{AOP}} = \dfrac{1}{2}(\dfrac{\tan(\dfrac{\pi}{2n})\tan(\dfrac{\pi}{n})}{\tan(\dfrac{\pi}{n}) + \tan(\dfrac{\pi}{2n})})r^2

tan ( π n ) = 2 tan ( π 2 n ) 1 tan 2 ( π 2 n ) \tan(\dfrac{\pi}{n}) = \dfrac{2\tan(\dfrac{\pi}{2n})}{1 - \tan^2(\dfrac{\pi}{2n})} \implies A A O P = tan ( π 2 n ) 3 tan 2 ( π 2 n ) r 2 A_{\triangle{AOP}} = \dfrac{\tan(\dfrac{\pi}{2n})}{3 - \tan^2(\dfrac{\pi}{2n})}r^2

A s t a r = 2 n tan ( π 2 n ) 3 tan 2 ( π 2 n ) r 2 \implies A_{star} = \dfrac{2n\tan(\dfrac{\pi}{2n})}{3 - \tan^2(\dfrac{\pi}{2n})}r^2

Let f = 2 n tan ( π 2 n ) 3 tan 2 ( π 2 n ) f = \dfrac{2n\tan(\dfrac{\pi}{2n})}{3 - \tan^2(\dfrac{\pi}{2n})} .

It will be shown that λ \lambda (slant angle) is independent f f .

Using the above diagram:

E G 2 = 2 r 2 ( 1 cos ( 4 π n ) = 4 sin 2 ( 2 π n ) r 2 E G = 2 sin ( 2 π n ) r EG^2 = 2r^2(1 - \cos(\dfrac{4\pi}{n}) = 4\sin^2(\dfrac{2\pi}{n})r^2 \implies EG = 2\sin(\dfrac{2\pi}{n})r O R = r 2 r 2 sin 2 ( 2 π n ) = r cos ( 2 π n ) \implies OR = \sqrt{r^2 - r^2\sin^2(\dfrac{2\pi}{n})} = r\cos(\dfrac{2\pi}{n}) and R Q = h 2 + r 2 cos 2 ( 2 π n ) RQ = \sqrt{h^2 + r^2\cos^2(\dfrac{2\pi}{n})}

\implies The lateral surface area A = n sin ( 2 π n ) r h 2 + r 2 cos 2 ( 2 π n ) A = n\sin(\dfrac{2\pi}{n})r\sqrt{h^2 + r^2\cos^2(\dfrac{2\pi}{n})}

The volume V = 1 3 f r 2 h = k k = 3 k f r 2 V = \dfrac{1}{3}fr^2h = k \implies k = \dfrac{3k}{fr^2} \implies A ( r ) = n sin ( 2 π n ) r 9 k 2 + f 2 cos 2 ( 2 π n ) r 6 A(r) = n\sin(\dfrac{2\pi}{n})r\sqrt{9k^2 + f^2\cos^2(\dfrac{2\pi}{n})r^6} \implies d A d r = ( n sin ( 2 π n ) ) 2 f 2 cos 2 ( 2 π n ) r 6 9 k 2 r 2 9 k 2 + f 2 cos 2 ( 2 π n ) r 6 r = ( 3 k 2 f cos ( 2 π n ) ) 1 3 \dfrac{dA}{dr} = (n\sin(\dfrac{2\pi}{n}))\dfrac{2f^2\cos^2(\dfrac{2\pi}{n})r^6 - 9k^2}{r^2\sqrt{9k^2 + f^2\cos^2(\dfrac{2\pi}{n})r^6}} \implies r = (\dfrac{3k}{\sqrt{2}f\cos(\dfrac{2\pi}{n})})^{\frac{1}{3}} h = 3 k f ( 2 f cos ( 2 π n ) 3 k ) 2 3 \implies h = \dfrac{3k}{f}(\dfrac{\sqrt{2} f\cos(\dfrac{2\pi}{n})}{3k})^{\frac{2}{3}}

Let λ \lambda be the measure of the angle between the slant height and the base.

tan ( λ ) = h O R = 2 λ 54.7356 \implies \tan(\lambda) = \dfrac{h}{OR} = \sqrt{2} \implies \lambda \approx \boxed{54.7356} .

Case 2: n n is an even positive integer 6 \geq 6 .

m A O B = π n m\angle{AOB} = \dfrac{\pi}{n} and by Inscribed Angle Theorem m Q B T = 1 2 m Q O T = 1 2 4 π n = 2 π n m A B O = π n m\angle{QBT} = \dfrac{1}{2}m\angle{QOT} = \dfrac{1}{2}\dfrac{4\pi}{n} = \dfrac{2\pi}{n} \implies m\angle{ABO} = \dfrac{\pi}{n} A O B \implies \triangle{AOB} is an isosceles triangle B C = O C = r 2 \implies BC = OC = \dfrac{r}{2} \implies tan ( π n ) = 2 h r h = r tan ( π n ) 2 \tan(\dfrac{\pi}{n}) = \dfrac{2h^{*}}{r} \implies h^{*} = \dfrac{r\tan(\dfrac{\pi}{n})}{2} \implies A A O B = 1 4 tan ( π n ) r 2 A s t a r = n 2 tan ( π n ) r 2 A_{\triangle{AOB}} = \dfrac{1}{4}\tan(\dfrac{\pi}{n})r^2 \implies A_{star} = \dfrac{n}{2}\tan(\dfrac{\pi}{n})r^2

Q T 2 = 2 r 2 ( 1 cos ( 4 π n ) ) = 4 sin 2 ( 2 π n ) r 2 Q T = 2 sin ( 2 π n ) r a = cos ( 2 π n ) r QT^2 = 2r^2(1 - \cos(\dfrac{4\pi}{n})) = 4\sin^2(\dfrac{2\pi}{n})r^2 \implies QT = 2\sin(\dfrac{2\pi}{n})r \implies a = \cos(\dfrac{2\pi}{n})r

P M = h 2 + cos 2 ( 2 π n ) r 2 \implies PM = \sqrt{h^2 + \cos^2(\dfrac{2\pi}{n})r^2} \implies

The surface area A = n sin ( 2 π n ) r h 2 + cos 2 ( 2 π n ) r 2 A = n\sin(\dfrac{2\pi}{n})r\sqrt{h^2 + \cos^2(\dfrac{2\pi}{n})r^2}

The volume V = n 6 tan ( π n ) r 2 h = k h = 6 k n tan ( π n ) r 2 V = \dfrac{n}{6}\tan(\dfrac{\pi}{n})r^2h = k \implies h = \dfrac{6k}{n\tan(\dfrac{\pi}{n})r^2}

Let f = n tan ( π n ) cos ( 2 π n ) f^{*} = n\tan(\dfrac{\pi}{n})\cos(\dfrac{2\pi}{n})

A ( r ) = 2 cos 2 ( π n ) \implies A(r) = 2\cos^2(\dfrac{\pi}{n}) 36 k 2 + f 2 r 6 r \dfrac{\sqrt{36k^2 + {f^{*}}^{2} r^6}}{r} \implies

d A d r = 4 cos 2 ( π n ) ( f 2 r 6 18 k 2 ) r 2 36 k 2 + f 2 r 6 = 0 \dfrac{dA}{dr} =\dfrac{4\cos^2(\dfrac{\pi}{n})({f^{*}}^{2} r^6 - 18k^2)}{r^2\sqrt{36k^2 + {f^{*}}^2r^6}} = 0

r = ( 3 2 k f ) 1 3 h = 6 k cos ( 2 π n ) f ( f 3 2 k ) 2 3 \implies r = (\dfrac{3\sqrt{2}k}{f^{*}})^{\frac{1}{3}} \implies h = \dfrac{6k\cos(\dfrac{2\pi}{n})}{f^{*}}(\dfrac{f^{*}}{3\sqrt{2}k})^{\frac{2}{3}}

Let θ \theta be the measure of the angle between the slant height and the base.

tan ( θ ) = h a = 2 λ = θ = 54.7356 \tan(\theta) = \dfrac{h}{a} = \sqrt{2} \implies \lambda = \theta = \boxed{54.7356}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...